Spatio-temporal modelling of shoreline migration in Sagar Island, West Bengal, India - Mondal, Ismail; Thakur, Sandeep; Juliev, Mukhiddin; Bandyopadhyay, Jatisankar; De, Tarun Kumar (Journal of coastal conservation, 2020)
Sagar Island is a very popular pilgrimage destination located in the western part of Indian Sundarbans. This study employs Digital Shoreline Analysis System (DSAS) extension tool in ArcGIS platform to study and analyse the shoreline dynamics of Sagar Island by utilizing satellite images extending 40 years (1975–2015). 44 transects with 100 m spacing were laid and divided into six littoral cells (LCs). End Point Rate (EPR) and Linear Regression (LR) models were utilized to analyze the shoreline change patterns and also for predicting the future shoreline positions. It was observed that almost the entire southern portion of Sagar Island is susceptible to high rate of shoreline erosion. Most of the erosion occurred in Dhablat (LC 4 (a)) in the south eastern part at a rate of 11.695 ± 2.1 m/year. The mean shoreline change rate was also high in LC5 (±23.525 m/year). However, the overall shoreline change rate for the island was 4.94 m/year and uncertainty of total shoreline change rate was ±4.4 m/year. The study shows the usefulness of DSAS as a scientific tool for shoreline change studies and highlights state of erosion in the study area.